Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Anatomy of the Middle and Late Miocene phase of Lake Megafazzan, central Sahara, southern Libya: lake margin deposits and environmental controls - Mark W. Hounslow; Nick Drake; Mustafa J. Salem; Simon J. Armitage; Helena E. White; Ahmed S. El-Hawat (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Applicability of next-generation risk assessment generic PBK models and their performance within the chemical domain - M. Spaenig; M. W. Ashraf; M. Bouhifd; C. Drake; T. Sobanski; S. E. Escher (Archives of Toxicology, 2026)
Physiologically based kinetic (PBK) models are a cornerstone of in vitro to in vivo extrapolation and are therefore central to next-generation risk assessment (NGRA). This study assesses the performance of a generic, high-throughput PBK model for 26 organic chemicals spanning a wide range of physicochemical properties. Model predictions based on standard in silico and in vitro input parameters were benchmarked against published, chemical-specific PBK models and in vivo kinetic data. Predicted plasma maximum concentrations (Cmax) were within tenfold of in vivo values for 50% of the chemicals and within threefold for 31%. Published PBK models generally showed closer agreement with in vivo Cmax, likely because they incorporate in vivo-derived kinetic parameters or chemical-specific kinetic processes. An analysis of the chemical space revealed a lipophilicity-dependent bias, where Cmax for lipophilic compounds tended to be underpredicted, whereas hydrophilic compounds were overpredicted. No other consistent trends were observed with respect to physicochemical or ADME descriptors, possibly reflecting the limited dataset size. Overall, while the generic PBK model workflow appears suitable for NGRA applications, the observed lipophilicity-dependent bias indicates that chemical-specific corrections or refinements may be required for more accurate predictions.

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Shoulder Kinematic and Muscle Activity Compensations to Scapular Stabilizer Weakness: An Optimal Control Framework - Matthew S. Russell; Daanish M. Mulla; Peter J. Keir; Edward K. Chadwick; Dimitra Blana; Janessa D. M. Drake; Jaclyn N. Chopp-Hurley (Annals of Biomedical Engineering, 2026)
Purpose Shoulder kinematic and muscular redundancy promotes considerable variability, obscuring possible insights into neuromuscular control and compensation mechanisms for muscle weakness or fatigue. The current study harnessed recent advancements in optimal control formulations for computational musculoskeletal models to determine potential neuromuscular control strategies to compensate for isolated muscle weakness. Methods A computational shoulder model characterized by independent clavicular, scapular, and humeral kinematics and 138 muscle elements was used. Optimal control-predicted thoracohumeral elevation kinematics were validated against published empirical kinematics. Force-generating capacity of the upper trapezius, middle trapezius, and lower trapezius, and serratus anterior were individually limited to 75%, 50%, and 25% maximal capacity to generate subsequent optimal control predictions of scapulothoracic kinematic changes associated with muscle weakness. Combined limited maximal force-generating capacity of lower trapezius and serratus anterior was also explored. Results Model-predicted scapulothoracic kinematics showed good agreement with reference data, yet some significant differences were identified below 55° thoracohumeral elevation. Fatigue-mediated kinematic changes were most apparent during sagittal plane elevation. Serratus anterior weakness displayed the largest scapulothoracic kinematic changes at all thresholds of limited force-generating capacity. It also prompted the largest compensatory muscle activity changes from other shoulder muscles, while upper trapezius weakness prompted very little compensatory changes in muscle activity. Conclusion Optimal control simulations were used to identify potential compensation mechanisms for shoulder muscle weakness and predict their effects on scapular kinematics. Findings suggest that thoracohumeral elevation in the scapular plane displayed less trapezius coactivity, both when ‘weakened’ and ‘unweakened.’ Thus, scapular plane tasks may isolate serratus anterior, while frontal plane tasks may achieve more balanced coactivation.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Assessing the intensity of Late Quaternary humid phases in the Nefud Desert, northern Arabia - Richard Clark‐Wilson; Simon J. Armitage; Ian Candy; Paul S. Breeze; Nick A. Drake; Huw S. Groucutt; Abdullah M. Alsharekh; Faisal Al‐Jibreen; Michael D. Petraglia; David B. Ryves (Journal of Quaternary Science, 2026)
The climate history of the major dryland zones of the world, such as the Saharo–Arabian Desert belt, plays a key role in the dispersal of early humans through these intermittently inhospitable regions. Here, we assess the relative intensity of Late Quaternary humid phases in northern Arabia through lithological, geochemical, palaeoecological and geochronological analysis of three sediment sequences in the Nefud Desert. Two sequences are marl beds that accumulated in perennial, groundwater‐fed lake systems during two distinct humid phases that occurred in MIS 5e and MIS 5a. The third records sediment accumulation within an ephemeral lake system during the terminal Pleistocene/early Holocene. The altitude of the two MIS 5 deposits indicates that the water table must have reached altitudes of >929 m ASL (MIS 5e) and >922 m ASL (MIS 5a). In contrast, the sedimentary characteristics of the early Holocene sequence imply that, during this interval, the water table was

Meta-analysis on microplastics monitoring in global water resource recovery facilities: An emphasis on overlooked factors - Elinor S. Austin; Dana M. Austin; Linda Y. Tseng; Lin Liu; Zeth Kleinmeyer; Danielle Drake; Diego Rosso; Yian Sun (Environmental Pollution, 2025)

Spatial atlasing of N-glycosylation in healthy control and clear cell renal cell carcinoma tissues linked with immune checkpoint inhibition response by MALDI mass spectrometry imaging - Caroline Kittrell; Lyndsay E.A. Young; Colin McDowell; Grace Grimsley; Anand S. Mehta; Peggi M. Angel; Jessica Schmitz; Nikolaos Vasileiadis; Christopher Darr; Viktor Grünwald; Philipp Ivanyi; Jan Hinrich Bräsen; et al. (Analytica Chimica Acta, 2025)

Latest Tortonian to early Pliocene interdune lake systems, southern Libya: Implications for the hydrology of the central Sahara - Mark W. Hounslow; Helena E. White; Nick Drake; Vassil Karloukovski; Sue J. McLaren; Mustafa J. Salem; Ahmed S. El-Hawat; Osama Hlal (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Late Quaternary inundation and desiccation of Megalake Chad traced in dust records from the Equatorial Atlantic Ocean - Anya J. Crocker; Christopher W. Kinsley; Amy M. Jewell; Paul S. Breeze; Nicholas A. Drake; David McGee; Charles S. Bristow; Katie Manning; Claudia Di Biagio; Paola Formenti; William R.C. Burton; Annie L. Murray; et al. (Quaternary Science Reviews, 2025)

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Outcomes from a DPD Consortium - S. Drake; P. McKeehan (Journal of the Academy of Nutrition and Dietetics, 2024)

Sr/Ca ratios indicate frugivory versus folivory in primates: a case study using handheld XRF in Kibale National Park, Uganda - M. I. Hamilton; B. L. Drake; E. Dzhinenko; A. Galloway; S. V. Nelson (Oecologia, 2024)

Preservation of plant‐wax biomarkers in deserts: implications for Quaternary environment and human evolutionary studies - Deepak Kumar Jha; Robert Patalano; Jana Ilgner; Hema Achyuthan; Abdullah M. Alsharekh; Simon Armitage; James Blinkhorn; Nicole Boivin; Paul S. Breeze; Ravindra Devra; Nicholas Drake; Huw S. Groucutt; et al. (Journal of Quaternary Science, 2024)
Analysis of plant‐wax biomarkers from sedimentary sequences can enable past environmental and hydrological reconstruction and provide insights into past hominin adaptations. However, biomarker preservation in desert contexts has been considered unlikely given the sparse nature of the vegetation within the landscape. Here we evaluate the preservation of n ‐alkanes and fatty acids collected from four depositional sequences associated with archaeological contexts in the Nefud Desert, Saudi Arabia, and the Thar Desert, India. Pleistocene and Holocene samples were selected to understand the effects of age on preservation. The results of molecular distribution patterns and indices, particularly the high carbon preference index and average chain length, show the preservation of plant‐wax biomarkers in both the Holocene and Pleistocene desert sequences, while δ 13 C values and organic content provide insights into the vegetation contributing to the plant‐wax organic pool. This study provides a baseline for understanding human–environment interactions and for reconstructing changes in arid land habitats of relevance to hominins during the Quaternary.

Propagating Uncertainty in Predicting Individuals and Means Illustrated with Foliar Chemistry and Forest Biomass - Ruth D. Yanai; John E. Drake; Hannah L. Buckley; Bradley S. Case; Paul J. Lilly; Richard C. Woollons; Javier G. P. Gamarra (Ecosystems, 2024)
Quantifying uncertainty is important to establishing the significance of comparisons, to making predictions with known confidence, and to identifying priorities for investment. However, uncertainty can be difficult to quantify correctly. While sampling error is commonly reported based on replicate measurements, the uncertainty in regression models used to estimate forest biomass from tree dimensions is commonly ignored and has sometimes been reported incorrectly, due either to lack of clarity in recommended procedures or to incentives to underestimate uncertainties. Even more rarely are the uncertainty in predicting individuals and the uncertainty in the mean both recognized for their contributions to overall uncertainty. In this paper, we demonstrate the effect of propagating these two sources of uncertainty using a simple example of calcium concentration of sugar maple foliage, which does not require regression, then the mass of foliage and calcium content of foliage, and finally an entire forest with multiple species and tissue types. The uncertainty due to predicting individuals is greater than the uncertainty in the mean for studies with few trees—up to 30 trees for foliar calcium concentration and 50 trees for foliar mass and calcium content in the data set we analyzed from the Hubbard Brook Experimental Forest. The most correct analysis will take both sources of uncertainty into account, but for practical purposes, country-level reports of uncertainty in carbon stocks can safely ignore the uncertainty in individuals, which becomes negligible with large enough numbers of trees. Ignoring the uncertainty in the mean will result in exaggerated confidence in estimates of forest biomass and carbon and nutrient contents.

Habitat fragmentation and the sporadic spread of pastoralism in the mid-Holocene Sahara - Katie Manning; Paul S. Breeze; Nick Drake; Julie Dunne; Emmanuelle Casanova; Richard P. Evershed (Quaternary Science Reviews, 2023)

Understanding the potential release of microplastics from coatings used on commercial ships - Mario N. Tamburri; Zhi Yang Soon; Christopher Scianni; Christer L. Øpstad; Neil S. Oxtoby; Simon Doran; Lisa A. Drake (Frontiers in Marine Science, 2022)
Microplastic pollution in the ocean is a critical, global environmental concern. Although believed to be a comparatively small contributor, the paints applied to commercial ships have been identified as a source of microplastics because polymers are used as binding agents in all anticorrosive and antifouling marine coatings. Furthermore, the release of microplastics from coatings may be amplified by in-water cleaning operations to remove biofouling. A comprehensive, detailed assessment and review of the array of commercial ships’ coatings, specifically characteristics, behavior, and fate over time, has not been conducted in the context of ocean microplastic pollution. This Policy Brief identifies gaps and proposes actions to better understand the fate of released particles with the goal to inform appropriate and effective solutions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Greenhouse gases and green roofs: carbon dioxide and methane fluxes in relation to substrate characteristics - Md Abdul Halim; Juliana Vantellingen; Adam S. Gorgolewski; William K. Rose; Jennifer A. P. Drake; Liat Margolis; Sean C. Thomas (Urban Ecosystems, 2022)

Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.

Risks of giant hogweed (Heracleum mantegazzianum) range increase in North America - K. Cuddington; S. Sobek-Swant; J. Drake; W. Lee; M. Brook (Biological Invasions, 2022)

Diet overlap of common and at-risk riverine benthic fishes before and after Round Goby (Neogobius melanostomus) invasion - B. L. Firth; M. S. Poesch; M. A. Koops; D. A. R. Drake; M. Power (Biological Invasions, 2021)

Accelerated invasion of decapod crustaceans in the southernmost point of the Atlantic coast of Europe: A non-natives’ hot spot? - Enrique González-Ortegón; Stuart Jenkins; Bella S. Galil; Pilar Drake; Jose A. Cuesta (Biological Invasions, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Angiotensin (1–7) delivered orally via probiotic, but not subcutaneously, benefits the gut-brain axis in older rats - Thomas W. Buford; Yi Sun; Lisa M. Roberts; Anisha Banerjee; Sujitha Peramsetty; Anthony Knighton; Amrisha Verma; Drake Morgan; Gonzalo E. Torres; Qiuhong Li; Christy S. Carter (GeroScience, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Fusarium solani haplotype 12‐b and aortic and branchial arteritis in Hippocampus erectus Perry - Tori Brown; Zach Millar; Drake Evans; Phuc H. Pham; Veronique LePage; John S. Lumsden (Journal of Fish Diseases, 2020)

Livestock manure driving stream nitrate - Christopher S. Jones; Chad W. Drake; Claire E. Hruby; Keith E. Schilling; Calvin F. Wolter (Ambio, 2019)

Individual field-collected glassy-winged sharpshooter vectors harbor sequences from two Xylella fastidiosa subspecies - Drake C. Stenger; Lindsey P. Burbank; Rodrigo Krugner; Mark S. Sisterson (European Journal of Plant Pathology, 2019)

Evaluation of wetted surface area of commercial ships as biofouling habitat flux to the United States - A. Whitman Miller; Ian C. Davidson; Mark S. Minton; Brian Steves; Cameron S. Moser; Lisa A. Drake; Gregory M. Ruiz (Biological Invasions, 2018)

Development of Plain Language Supplemental Materials for the Biobank Informed Consent Process - Bettina F. Drake; Katherine M. Brown; Sarah Gehlert; Leslie E. Wolf; Joann Seo; Hannah Perkins; Melody S. Goodman; Kimberly A. Kaphingst (Journal of Cancer Education, 2017)

Ventral-aspect radar cross sections and polarization patterns of insects at X band and their relation to size and form - V. A. Drake; J. W. Chapman; K. S. Lim; D. R. Reynolds; J. R. Riley; A. D. Smith (International Journal of Remote Sensing, 2017)

Genomic Diversity of Type B3 Bacteriophages of Caulobacter crescentus - Kurt T. Ash; Kristina M. Drake; Whitney S. Gibbs; Bert Ely (Current Microbiology, 2017)

Quantifying the extent of niche areas in the global fleet of commercial ships: the potential for “super-hot spots” of biofouling - Cameron S. Moser; Timothy P. Wier; Matthew R. First; Jonathan F. Grant; Scott C. Riley; Stephanie H. Robbins-Wamsley; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2017)

Four generations of SDHB-related disease: complexities in management - U. Srirangalingam; M. LeCain; N. Tufton; S. A. Akker; W. M. Drake; K. Metcalfe (Familial Cancer, 2017)

The marine cytotoxin portimine is a potent and selective inducer of apoptosis - Sarah L. Cuddihy; Sarah Drake; D. Tim Harwood; Andrew I. Selwood; Paul S. McNabb; Mark B. Hampton (Apoptosis, 2016)

Allometry data and equations for coastal marsh plants - Meng Lu; Joshua S. Caplan; Jonathan D. Bakker; J. Adam Langley; Thomas J. Mozdzer; Bert G. Drake; J. Patrick Megonigal (Ecology, 2016)
Coastal marshes are highly valued for ecosystem services such as protecting inland habitats from storms, sequestering carbon, removing nutrients and other pollutants from surface water, and providing habitat for fish, shellfish, and birds. Because plants largely determine the structure and function of coastal marshes, quantifying plant biomass is essential for evaluating these ecosystem services, understanding the biogeochemical processes that regulate ecosystem function, and forecasting tidal wetland responses to accelerated sea level rise. Allometry is a convenient and efficient technique for nondestructive estimation of plant biomass, and it is commonly used in studies of carbon and nitrogen cycles, energy flows, and marsh surface elevation change. We present plant allometry data and models developed for three long‐term experiments at the Smithsonian Global Change Research Wetland, a brackish marsh in the Rhode River subestuary of the Chesapeake Bay. The dataset contains 9,771 measurements of stem height, dry mass, and (in 9638 cases) stem width across 11 plant species. The vast majority of observations are for Schoenoplectus americanus (8430) and Phragmites australis (311), with fewer observations for other common species: Amaranthus cannabinus , Atriplex patula , Iva frutescens , Kosteletzkya virginica , Polygonum hydropiper , Solidago sempervirens , Spartina alterniflora , Spartina cynosuroides , and Typha angustifolia . Allometric relationships take the form of linear regressions of biomass (transformed using the Box‐Cox procedure) on either stem height and width, or on stem height alone. Allometric relationships for Schoenoplectus americanus were not meaningfully altered by elevated CO 2 , N enrichment, the community context, interannual variation in climate, or year, showing that a single equation can be used across a broad range of conditions for this species. Archived files include: (1) raw data used to derive allometric equations for each species, (2) reports and evaluations of the allometric equations we derived from the data, and (3) R code with which our derivations can be replicated. Methodological details of our experiments, data collection efforts, and statistical modeling are described in the metadata. The allometric equations can be used for biomass estimation in empirical and modeling studies of North American coastal wetlands, and the data can be used in ecological studies of terrestrial plant allometry.

Human occupation of the northern Arabian interior during early Marine Isotope Stage 3 - Richard P. Jennings; Ash Parton; Laine Clark‐Balzan; Tom S. White; Huw S. Groucutt; Paul S. Breeze; Adrian G. Parker; Nick A. Drake; Michael D. Petraglia (Journal of Quaternary Science, 2016)
The early part of Marine Isotope Stage (MIS) 3 (ca. 60–50 ka) is a crucial period for studying human demography and behaviour in south‐west Asia, and how these relate to climatic changes. However, the archaeological and palaeoenvironmental records for MIS 3 in critical areas such as the Arabian Peninsula remain poorly developed. Here, we present findings from the Al Marrat basin in the Nefud desert, which provides the first clear evidence for both increased humidity and human occupation of the interior of northern Arabia during early MIS 3. A Middle Palaeolithic assemblage, dated by optically stimulated luminescence to ca . 55 ka, was found stratified within a sequence of relict palustrine deposits indicative of shallow water body formation in the Al Marrat basin. Hominin presence in northern Arabia at this time coincides with the intensification and northward displacement of monsoon rainfall systems during a period of maximum insolation. These findings add to a growing corpus of palaeoenvironmental evidence, which indicates that the Arabian interior was neither arid nor unpopulated during early MIS 3, and that hydrodynamic responses to enhanced moisture availability facilitated demographic expansions into the Arabian interior.

Formate‐derived H 2 , a driver of hydrogenotrophic processes in the root‐zone of a methane‐emitting fen - Sindy Hunger; Oliver Schmidt; Anita S. Gößner; Harold L. Drake (Environmental Microbiology, 2016)
Summary Wetlands are important sources of globally emitted methane. Plants mediate much of that emission by releasing root‐derived organic carbon, including formate, a direct precursor of methane. Thus, the objective of this study was to resolve formate‐driven processes potentially linked to methanogenesis in the fen root‐zone. Although, formate was anticipated to directly trigger methanogenesis, the rapid anaerobic consumption of formate by Carex roots unexpectedly yielded H 2 and CO 2 via enzymes such as formate‐H 2 ‐lyase (FHL), and likewise appeared to enhance the utilization of organic carbon. Collectively, 57 [FeFe]‐ and [NiFe]‐hydrogenase‐containing family level phylotypes potentially linked to FHL activity were detected. Under anoxic conditions, root‐derived fermentative Citrobacter and Hafnia isolates produced H 2 from formate via FHL. Formate‐derived H 2 fueled methanogenesis and acetogenesis, and methanogenic ( Methanoregula , Methanobacterium , Methanocella ) and acetogenic ( Acetonema , Clostridum , Sporomusa ) genera potentially linked to these hydrogenotrophic activities were identified. The findings (i) provide novel insights on highly diverse root‐associated FHL‐containing taxa that can augment secondary hydrogenotrophic processes via the production of formate‐derived H 2 , (ii) demonstrate that formate can have a ‘priming’ effect on the utilization of organic carbon, and (iii) raise questions regarding the fate of formate‐derived H 2 when it diffuses away from the root‐zone.

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Differences in preferences for models of consent for biobanks between Black and White women - Katherine M. Brown; Bettina F. Drake; Sarah Gehlert; Leslie E. Wolf; James DuBois; Joann Seo; Krista Woodward; Hannah Perkins; Melody S. Goodman; Kimberly A. Kaphingst (Journal of Community Genetics, 2016)

Quantifying the total wetted surface area of the world fleet: a first step in determining the potential extent of ships’ biofouling - Cameron S. Moser; Timothy P. Wier; Jonathan F. Grant; Matthew R. First; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2016)

Short‐term carbon cycling responses of a mature eucalypt woodland to gradual stepwise enrichment of atmospheric CO 2 concentration - John E. Drake; Catriona A. Macdonald; Mark G. Tjoelker; Kristine Y. Crous; Teresa E. Gimeno; Brajesh K. Singh; Peter B. Reich; Ian C. Anderson; David S. Ellsworth (Global Change Biology, 2016)
Projections of future climate are highly sensitive to uncertainties regarding carbon (C) uptake and storage by terrestrial ecosystems. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment was established to study the effects of elevated atmospheric CO 2 concentrations (eCO 2 ) on a native mature eucalypt woodland with low fertility soils in southeast Australia. In contrast to other FACE experiments, the concentration of CO 2 at Euc FACE was increased gradually in steps above ambient (+0, 30, 60, 90, 120, and 150 ppm CO 2 above ambient of ~400 ppm), with each step lasting approximately 5 weeks. This provided a unique opportunity to study the short‐term (weeks to months) response of C cycle flux components to eCO 2 across a range of CO 2 concentrations in an intact ecosystem. Soil CO 2 efflux (i.e., soil respiration or R soil ) increased in response to initial enrichment (e.g., +30 and +60 ppm CO 2 ) but did not continue to increase as the CO 2 enrichment was stepped up to higher concentrations. Light‐saturated photosynthesis of canopy leaves ( A sat ) also showed similar stimulation by elevated CO 2 at +60 ppm as at +150 ppm CO 2 . The lack of significant effects of eCO 2 on soil moisture, microbial biomass, or activity suggests that the increase in R soil likely reflected increased root and rhizosphere respiration rather than increased microbial decomposition of soil organic matter. This rapid increase in R soil suggests that under eCO 2, additional photosynthate was produced, transported belowground, and respired. The consequences of this increased belowground activity and whether it is sustained through time in mature ecosystems under eCO 2 are a priority for future research.

A Community Coalition to Address Cancer Disparities: Transitions, Successes and Challenges - Vetta L. Sanders Thompson; Bettina Drake; Aimee S. James; Monique Norfolk; Melody Goodman; Leon Ashford; Sherrill Jackson; Miranda Witherspoon; Mikki Brewster; Graham Colditz (Journal of Cancer Education, 2015)

Erratum to: Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Immigration can destabilize tri-trophic interactions: implications for conservation of top predators - Kevin L. S. Drury; Jesse D. Suter; Jacob B. Rendall; Andrew M. Kramer; John M. Drake (Theoretical Ecology, 2015)

Evidence for the persistence of food web structure after amphibian extirpation in a Neotropical stream - Thomas R. Barnum; John M. Drake; Checo Colón-Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; Catherine M. Pringle (Ecology, 2015)
Species losses are predicted to simplify food web structure, and disease‐driven amphibian declines in Central America offer an opportunity to test this prediction. Assessment of insect community composition, combined with gut content analyses, was used to generate periphyton–insect food webs for a Panamanian stream, both pre‐ and post‐amphibian decline. We then used network analysis to assess the effects of amphibian declines on food web structure. Although 48% of consumer taxa, including many insect taxa, were lost between pre‐ and post‐amphibian decline sampling dates, connectance declined by less than 3%. We then quantified the resilience of food web structure by calculating the number of expected cascading extirpations from the loss of tadpoles. This analysis showed the expected effects of species loss on connectance and linkage density to be more than 60% and 40%, respectively, than were actually observed. Instead, new trophic linkages in the post‐decline food web reorganized the food web topology, changing the identity of “hub” taxa, and consequently reducing the effects of amphibian declines on many food web attributes. Resilience of food web attributes was driven by a combination of changes in consumer diets, particularly those of insect predators, as well as the appearance of generalist insect consumers, suggesting that food web structure is maintained by factors independent of the original trophic linkages.

Differential dispersal shapes population structure and patterns of genetic differentiation in two sympatric pond breeding salamanders - William E. Peterman; Thomas L. Anderson; Brittany H. Ousterhout; Dana L. Drake; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics, 2015)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Thermal sensitivity across ages and during chronic fentanyl administration in rats - Jeremiah D. Mitzelfelt; Christy S. Carter; Drake Morgan (Psychopharmacology, 2014)

Integrin α3β1 regulates tumor cell responses to stromal cells and can function to suppress prostate cancer metastatic colonization - Afshin Varzavand; Justin M. Drake; Robert U. Svensson; Mary E. Herndon; Bo Zhou; Michael D. Henry; Christopher S. Stipp (Clinical & Experimental Metastasis, 2013)

The propagation and dispersal of misinformation in ecology: Is there a relationship between citation accuracy and journal impact factor? - D. C. Drake; B. Maritz; S. M. Jacobs; C. J. Crous; A. Engelbrecht; A. Etale; M. J. Fourie; D. G. Furniss; S. L. Scott; S. Parusnath; D. R. Tye (Hydrobiologia, 2013)

The near-term risk of climate uncertainty among the U.S. states - George A. Backus; Thomas S. Lowry; Drake E. Warren (Climatic Change, 2013)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

Identification of clinical isolates of anaerobic bacteria using matrix-assisted laser desorption ionization-time of flight mass spectrometry - D. P. Fedorko; S. K. Drake; F. Stock; P. R. Murray (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Early life sun exposure, vitamin D-related gene variants, and risk of non-Hodgkin lymphoma - Jennifer L. Kelly; Matthew T. Drake; Zachary S. Fredericksen; Yan W. Asmann; Mark Liebow; Tait D. Shanafelt; Andrew L. Feldman; Stephen M. Ansell; William R. Macon; Megan M. Herr; Alice H. Wang; Grzegorz S. Nowakowski; et al. (Cancer Causes & Control, 2012)

Conservation status of eulachon in the California Current - Richard G Gustafson; Michael J Ford; Peter B Adams; Jonathan S Drake; Robert L Emmett; Kurt L Fresh; Mindy Rowse; Elizabeth A K Spangler; Robert E Spangler; David J Teel; Matthew T Wilson (Fish and Fisheries, 2012)
Eulachon ( Thaleichthys pacificus ), an anadromous smelt in the Northeast Pacific Ocean was examined for listing under the USA’s Endangered Species Act (ESA). A southern Distinct Population Segment (DPS) of eulachon – that occurs in the California Current and is composed of numerous subpopulations that spawn in rivers from northern California to northern British Columbia – was identified on the basis of ecological and environmental characteristics, and to a lesser extent, genetic and life history variation. Although the northern terrestrial boundary of this DPS remains uncertain, our consensus opinion was that this northern boundary occurs south of the Nass River and that the DPS was discrete from more northern eulachon, as well as significant to the biological species as a whole and thus is a ‘species’ under the ESA. Eulachon have been nearly absent in northern California for over two decades, have declined in the Fraser River by over 97% in the past 10 years, and are at historically low levels in other British Columbia rivers in the DPS, and nearly so in the Columbia River. Major threats to southern eulachon include climate change impacts on ocean and freshwater habitat, by‐catch in offshore shrimp trawl fisheries, changes in downstream flow timing and intensity owing to dams and water diversions, and predation. These threats, together with large declines in abundance, indicate that the southern DPS of eulachon is at moderate risk of extinction throughout all of its range. The southern DPS was listed as threatened under the ESA in May 2010 – the first marine forage fish to be afforded these statutory protections, which apply only to waters under U.S. jurisdiction.

Water use and water-use efficiency of coppice and seedling Eucalyptus globulus Labill.: a comparison of stand-scale water balance components - Paul L. Drake; Daniel S. Mendham; Don A. White; Gary N. Ogden; Bernard Dell (Plant and Soil, 2012)

Imprint switch mutations at Rasgrf1 support conflict hypothesis of imprinting and define a growth control mechanism upstream of IGF1 - Nadia M. Drake; Yoon Jung Park; Aditya S. Shirali; Thomas A. Cleland; Paul D. Soloway (Mammalian Genome, 2009)

Potential health impacts of heavy-metal exposure at the Tar Creek Superfund site, Ottawa County, Oklahoma - John S. Neuberger; Stephen C. Hu; K. David Drake; Rebecca Jim (Environmental Geochemistry and Health, 2009)

Cocaine self-administration on a hold-down schedule of reinforcement in rats - Drake Morgan; Yu Liu; Erik B. Oleson; David C. S. Roberts (Psychopharmacology, 2009)

Cross-sensitization of the reinforcing effects of cocaine and amphetamine in rats - Yu Liu; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2007)

Functional Richness and Relative Resilience of Bird Communities in Regions with Different Land Use Intensities - J. Fischer; D. B. Lindenmayer; S. P. Blomberg; R. Montague-Drake; A. Felton; J. A. Stein (Ecosystems, 2007)

Production of Landsat ETM+ reference imagery of burned areas within Southern African savannahs: comparison of methods and application to MODIS - A. M. S. Smith; N. A. Drake; M. J. Wooster; A. T. Hudak; Z. A. Holden; C. J. Gibbons (International Journal of Remote Sensing, 2007)

Demographic Stochasticity, Environmental Variability, and Windows of Invasion Risk for Bythotrephes Longimanus in North America - John M. Drake; Kevin L. S. Drury; David M. Lodge; Agnes Blukacz; N. D. Yan; Greg Dwyer (Biological Invasions, 2006)

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

Effects of extended-access self-administration and deprivation on breakpoints maintained by cocaine in rats - Yu Liu; David C. S. Roberts; Drake Morgan (Psychopharmacology, 2005)

Comparative Aquatic Toxicity Evaluation of 2-(Thiocyanomethylthio)benzothiazole and Selected Degradation Products Using Ceriodaphnia dubia - S. T. Nawrocki; K. D. Drake; C. F. Watson; G. D. Foster; K. J. Maier (Archives of Environmental Contamination and Toxicology, 2005)

Binge self-administration and deprivation produces sensitization to the reinforcing effects of cocaine in rats - Drake Morgan; Mark A. Smith; David C. S. Roberts (Psychopharmacology, 2005)

Effects of positive allosteric modulators of the GABA B receptor on cocaine self-administration in rats - Mark A. Smith; David L. Yancey; Drake Morgan; Yu Liu; Wolfgang Froestl; David C. S. Roberts (Psychopharmacology, 2004)

The clonal structure of Quercus geminata revealed by conserved microsatellite loci - E. A. Ainsworth; P. J. Tranel; B. G. Drake; S. P. Long (Molecular Ecology, 2003)
The scrub oak communities of the southeastern USA may have existed at their present locations for thousands of years. These oaks form suckers, and excavations of root systems suggest that clones may occupy very large areas. Resolution of the clonal nature of scrub oaks is important both to manage the tracts of this ecosystem that remain, and in conducting long‐term ecological studies, where the study area must substantially exceed the area occupied by any single clone. Microsatellites were used to determine the genetic diversity of a dominant oak species within a 2‐ha long‐term experimental site on Merritt Island at the Kennedy Space Center. This area contains a long‐term study of the effects of elevated CO 2 on the ecosystem. Conservation of seven microsatellite loci, previously identified in the sessile oak, Quercus petraea , was tested in two Florida scrub oak species, Q. geminata and Q. myrtifolia . Sequence analysis revealed that all seven microsatellite loci were conserved in Q. geminata and five loci were conserved in Q. myrtifolia . Six microsatellite loci were polymorphic in Q. geminata and these were subsequently used to investigate the clonal structure of the Q. geminata population. Twenty‐one unique combinations of microsatellites, or haplotypes, occurred only once, whereas the remaining 26 individuals belonged to a total of seven different haplotypes. Trees with identical haplotypes were in close proximity, supporting the interpretation that they were clones. The results showed that there is significant genetic diversity within the 2‐ha experimental site. Microsatellites provided a powerful and noninvasive tool for distinguishing individual genotypes and determining an adequate area for long‐term ecosystem studies.

Cocaine- and food-maintained responding under a multiple schedule in rhesus monkeys: environmental context and the effects of a dopamine antagonist - Michael A. Nader; Rachna S. Sinnott; Robert H. Mach; Drake Morgan (Psychopharmacology, 2002)

Self-administration of two long-acting monoamine transport blockers in rhesus monkeys - Joshua A. Lile; Drake Morgan; Cory S. Freedland; Rachna S. Sinnott; Huw M.L. Davies; Michael A. Nader (Psychopharmacology, 2000)

Impact of Human Activity on Regional Forest Composition and Dynamics in Central New England - Janice L. Fuller; David R. Foster; Jason S. McLachlan; Natalie Drake (Ecosystems, 1998)

Short‐term decomposition of litter produced by plants grown in ambient and elevated atmospheric CO 2 concentrations - S. BALL; BERT DRAKE (Global Change Biology, 1997)
The effects of elevated atmospheric CO 2 (ambient + 340 μmol mol –1 ) on above‐ground litter decomposition were investigated over a 6‐week period using a field‐based mesocosm system. Soil respiratory activity in mesocosms incubated in ambient and elevated atmospheric CO 2 concentrations were not significantly different ( t ‐test, P > 0.05) indicating that there were no direct effects of elevated atmospheric CO 2 on litter decomposition. A study of the indirect effects of CO 2 on soil respiration showed that soil mesocosms to which naturally senescent plant litter had been added (0.5% w/w) from the C 3 sedge Scirpus olneyi grown in elevated atmospheric CO 2 was reduced by an average of 17% throughout the study when compared to soil mesocosms to which litter from Scirpus olneyi grown in ambient conditions had been added. In contrast, similar experiments using senescent material from the C 4 grass Spartina patens showed no difference in soil respiration rates between mesocosms to which litter from plants grown in elevated or ambient CO 2 conditions had been added. Analysis of the C:N ratio and lignin content of the senescent material showed that, while the C:N ratio and lignin content of the Spartina patens litter did not vary with atmospheric CO 2 conditions, the C:N ratio (but not the lignin content) of the litter from Scirpus olneyi was significantly greater ( t ‐test; P 2 (105:1 compared to 86:1 for litter derived from Scirpus olneyi grown under ambient conditions). The results suggest that the increased C:N ratio of the litter from the C 3 plant Scirpus olneyi grown under elevated CO 2 led to the lower rates of biodegradation observed as reduced soil respiration in the mesocosms. Further long‐term experiments are now required to determine the effects of elevated CO 2 on C partitioning in terrestrial ecosystems.